2018
DOI: 10.5937/gp22-16988
|View full text |Cite
|
Sign up to set email alerts
|

Migrant remittances and their impact on the economic development of the Baltic states

Abstract: This paper studies the determinants of international migration and remittances in the Baltic States (represented hereinafter by Lithuania, Latvia, and Estonia). The research reveals a critical view on migrant remittances in terms of macroeconomic development and social conditions in the society of each country involved into our research. In order to investigate and to demonstrate the impact of migrant remittances on GDP and consumption compared with current account balance, minimal wages, and foreign direct in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 25 publications
5
25
0
2
Order By: Relevance
“…It has been discussed earlier that remittance serves as an engine for economic growth and better environment (Rausser et al, 2018). Gibson and McKenzie (2010) found that the typical yearly value of remittance is approximately 5000$.…”
Section: Economic Impact On the Sending Countriesmentioning
confidence: 96%
See 4 more Smart Citations
“…It has been discussed earlier that remittance serves as an engine for economic growth and better environment (Rausser et al, 2018). Gibson and McKenzie (2010) found that the typical yearly value of remittance is approximately 5000$.…”
Section: Economic Impact On the Sending Countriesmentioning
confidence: 96%
“…These findings were supported by Simionescu (2016) and Kroeger (2015) as well. Inauspicious social environment evolved in every post-communist country since the 70's, but it remained tacit until the actual transition to market economy and democratisation had not started (Rausser et al;Papadopoulos, 2011).…”
Section: Pillars Of Migrationmentioning
confidence: 99%
See 3 more Smart Citations